Analysis of Determinants and Factors Affecting Indonesian Soybean Imports - Indah Adelina Siregar; Rahmi Nofitasari; Indah Kartika Sandra (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Soybeans are the main food commodity for Indonesian people after rice and corn. Indonesia's population growth every year shows an increase in the need for food, which results in an increase in demand for soybeans. On the other hand, Indonesia's soybean production is experiencing a decline, which has a negative impact on the industry and forces the government to import soybeans from abroad. The objectives of this study are: (1) to scrutinize in part the effects of import prices, land area, production, consumption, and exchange rates on Indonesian soybean imports, (2) The Role of Pricing in Moderating the Impact of Consumption on Indonesian Soybean Imports. analysis in this study, secondary data from BPS, the World Bank, UN Comtrade, and pertinent publications were combined with multiple linear regression. Multiple linear regression and moderation were used in the data analysis process with the software used Eviews 12. The analysis method for this research uses des.cr.iptive analysis, validity and reliability. The research results show that in Indonesia, partially the quantity of imported soybeans has a significant influence on the exchange rate variables, household consumption, import prices and consumption interactions. In the meanwhile, the variables related to production and land are.a do. not significantly affect the amount of soybeans imported into Indonesia. The study's findings demonstrate that import prices have a major impact on Indonesia's imports of soybeans.